Pengembangan Sistem Informasi Gadai Enoni Cell Berbasis Web - Geovanda, Benedictus; Lau, Reyon; Yunita, Rahmah; Haryono, Wasis (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2025)
The advancement of information technology has driven digital transformation across various sectors, including pawn services. Enoni Cell, a microenterprise engaged in electronic goods pawning, still relies on a manual recording system, leading to frequent errors, delayed services, and difficulties in data tracking. This study aims to develop a web-based pawn information system to improve operational efficiency and service quality. The system covers customer registration, item data entry, pawn period extensions, and redemption processes, all accessible in real time by both administrators and customers. The development method used is the waterfall model, consisting of requirements analysis, design, implementation, testing, and maintenance phases. The results show that the system accelerates administrative processes, reduces errors, and enhances information accessibility. This research contributes to improving service professionalism and supports digital transformation in microenterprises such as Enoni Cell.